Barro cocido - Taller de cine UNL (Taller de cine UNL, 2021)
Con: Rogelio Alaniz, Benito Rolón, Huberto Torres, Claudio Bustos, Francisco Ramírez, Roberto Trucco, Ernesto Ruiz, Teresita Cherry Basado en cuento de Juan José Saer